Studi Tela'ah Konsep Teologi Islam dan Gender Muhammad Shahrour - Nurhanipah Harahap Hanipah (ZARATHUSTRA (Jurnal Sosiologi dan Filsafat), 2023)
This paper aims to examine the theory of thought of one of the intellectual figures from Damascus, Syria namely Muhammad Shahrour by focusing on issues concerning Islamic theology and gender. This research is a type of library research using descriptive research methods. The data collection in this research is by collecting data related to the theme. The results of this research are, the emergence of Shahrour's theoretical thoughts begins with Shahrour's observations regarding problems that occur among Muslims, especially related to the application of modernity which is not easy to implement. taught. This is what makes Shahrour inseparable from the existence of his turats which is a fixed price. On this basis, Shahrour came up with a change movement that aims to re-interpret the messages contained in the Qur'an. Besides that, this movement was also carried out to shed turats fanaticism which made it difficult for Islam to progress. To help support this movement, it is based on a linguistic theory which, according to Shahrour, language has no language in common. Moving on from this, Shahrour then said that if an Islamic scientific tradition during the Islamic period was scientific. From this scientific Islam, a new thought was born regarding the concept of Islamic theology and gender which so far was considered irrelevant to face the challenges of modernity so that the concept of Islamic theology is universal, then progresses and in the process of its development it can be accepted by every human being.